KEKONVERGENAN BARISAN DI RUANG HILBERT PADA PEMETAAN TIPE-NONSPREADING DAN NONEXPANSIVE - Debi Oktia Haryeni (Jurnal Matematika UNAND, 2013)
We obtained some fundamental properties for k-strictly pseudononspreadingmappings in Hilbert space. Furthermore, we studied the approximation of commonxed points of k-strictly pseudononspreading mappings and nonexpansive mappings ina Hilbert space using the iterative scheme.